Effect of Social Support Program Using Application Line to Stress of Aging in the COVID - 19 Situation - Thansuk , Chaisit; Phimphanchaiyaboon , Lunchana (Journal of Nursing, Siam University, 2024)
The purpose of this quasi-experimental study was to examine the effect of the social support program using line application on stress among the aging in The Senior Citizen Association of Nursing Siam University. The Thai 36 aging participants were purposively recruited according to the criteria and simply randomized in an experiment. 18 of them were randomly assigned to either the experimental or the control group. The experimental group received the social support program using line application while the control group received the usual care. Data were collected from both groups at pre-test, post-test period from December 2022 to January 2023. Instruments included the SPST-20 (Suanprung Stress Test-20) with its Cronbach’s alpha was .87, and social support program using group process. Descriptive statistics and Independent Samples t-test were applied analyze the data. The results revealed that the stress of aging mean score of the experimental group was significantly different from those in the control group (p < .05). The stress mean scores at post-test and at follow up period in the experimental group were significantly lower than at pre-test as well as lower than those of the control group (p < .001). The results of this study indicated that a social support program using line application was able to reduce the feeling of stress in the aging.